Adult tetanus in the 21st century: Where are we? case series and review - Abdul Karim, Othman; Mohd Shazli, Draman @yusof; Mohd Nazri, Ali (2019)
Objective: To review cases of severe adult tetanus admitted to intensive care unit (ICU) and describe clinical features, etiologic factors and outcome of 2 patients with the diagnosis of severe adult tetanus. Study Design: A retrospective case series. Methods: Medical records of patients admitted with severe tetanus to adult intensive care Hospital Raja Perempuan Zainab 2 (HRPZ 2) in 2018 were reviewed. Results: 2 patients were identified, aged of 18 years old and 72 years old. Both patients presented to our care after 14 days of alleged cut by scrap metal with clinical features of severe tetanus and multiorgan impairment. However, the elderly patient developed a life-threatening autonomic disturbance. Despite good improvement of their clinical condition, the elderly patient was discharged from intensive care unit after 41 days of admission, whereas the younger patient was discharged from intensive care unit after 7 days of admission. Conclusion: Adult tetanus will remain a relevant and important disease in the 21st century. With the advancement of care in the intensive care unit, there is a shift in a cause of death that is from acute airway obstruction, respiratory failure and renal failure as a prominent cause of death to a complication of autonomic disturbance and intensive care related complications with include nosocomial infection, sepsis and complications of prolonged stay in intensive care unit. Lack of definitive randomized control trial, with a significant lack of familiarity and compliance to tetanus prophylactic among physicians will remain as a major issue in managing tetanus in the 21st century. This issue is further complicated by a gradual loss of immunity to tetanus among elderly population.